Pereduksian Rasionalitas dan Fungsi Rasionalitas Emotif dalam Teori Pilihan Rasional pada Kajian Ekonomi Hukum - Teddy Asmara (Fakultas Hukum, Universitas Islam Bandung, 2011)
The mental block of behavioral approach when implemented rational choice theory in economic law studies is actually reflection of its unrealistic core assumption: that people subject to law act rationally. That assumption or postulate is deductively elaborated into crudely conception of economic and psychological, and it is nothing else but necessarily to hold their paradigms that reasoned out the human frame of reference in an incentive-disincentive mechanism or the stimuli-respond design. No doubt the results of research that insisted arbitrary concepts and ignored inductive method would be artificial and partial nature, and essential dehumanization, or that research based on economy or psychology concept alone is not sufficient to accout for legal behaviour processes. Hence, legal economic scholars should established analysis the mind and act linkage through thick description, for example, by followed anthropology discipline has commited to holistic explanation, look at the people’s entity as it is in realities.